2019
DOI: 10.7717/peerj.7466
|View full text |Cite
|
Sign up to set email alerts
|

The effects of detraining and retraining periods on fat-mass and fat-free mass in elite male soccer players

Abstract: The aim of the study was to examine the effects of a detraining period (DTP) (i.e., off-season) with an individually prescribed training program, and a retraining period (RTP) (i.e., pre-season) combining soccer and flywheel-based strength training on fat-free mass (FFM) and fat-mass (FM) in 10 elite professional male soccer players. The present study used a controlled repeated-measures research design to investigate the changes in FFM and FM using dual-energy X-ray absorptiometry. Whole body %FM increased (ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 45 publications
1
43
0
2
Order By: Relevance
“…It is possible to speculate that these conditions resemble or even exacerbate off-training physical behaviors of athletes (Sperlich and Holmberg, 2017 ; Izzicupo et al, 2019 ). Studies on vascular, metabolic, and muscular adaptations to unloading (e.g., uninterrupted sitting and bed rest) as well as on post-injury conditions (Milsom et al, 2014 ) or the detrimental effects of the off-season (Suarez-Arrones et al, 2019 ) allow some speculations. Findings indicate that prolonged and uninterrupted sitting is associated with body fatness in highly trained athletes (Júdice et al, 2014 ); acute lower limbs dysfunction in healthy young subjects (Padilla and Fadel, 2017 ); increased sympathetic and renin–angiotensin system activity (Young and Leicht, 2011 ), plasma fibrinogen (Izzicupo et al, 2020 ), hematocrit, hemoglobin, and red blood cell count and a reduction in plasma volume (Howard et al, 2013 ); modified glucose and lipid metabolisms (Bergouignan et al, 2009 ; Stephens et al, 2011 ); changes in muscle size and architecture and tendon mechanical properties (De Boer et al, 2007 ; de Boer et al, 2008 ); muscle loss (Miles et al, 2005 ); and reductions in muscle strength, power, and rate of force development (Mujika and Padilla, 2001 ; De Boer et al, 2007 ; Bosquet et al, 2013 ; Rejc et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to speculate that these conditions resemble or even exacerbate off-training physical behaviors of athletes (Sperlich and Holmberg, 2017 ; Izzicupo et al, 2019 ). Studies on vascular, metabolic, and muscular adaptations to unloading (e.g., uninterrupted sitting and bed rest) as well as on post-injury conditions (Milsom et al, 2014 ) or the detrimental effects of the off-season (Suarez-Arrones et al, 2019 ) allow some speculations. Findings indicate that prolonged and uninterrupted sitting is associated with body fatness in highly trained athletes (Júdice et al, 2014 ); acute lower limbs dysfunction in healthy young subjects (Padilla and Fadel, 2017 ); increased sympathetic and renin–angiotensin system activity (Young and Leicht, 2011 ), plasma fibrinogen (Izzicupo et al, 2020 ), hematocrit, hemoglobin, and red blood cell count and a reduction in plasma volume (Howard et al, 2013 ); modified glucose and lipid metabolisms (Bergouignan et al, 2009 ; Stephens et al, 2011 ); changes in muscle size and architecture and tendon mechanical properties (De Boer et al, 2007 ; de Boer et al, 2008 ); muscle loss (Miles et al, 2005 ); and reductions in muscle strength, power, and rate of force development (Mujika and Padilla, 2001 ; De Boer et al, 2007 ; Bosquet et al, 2013 ; Rejc et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are different time points throughout the season where players may need to manipulate their intake to illicit changes in fat mass (FM) or skeletal muscle mass (fat free soft tissue mass (FFSTM)). 156 This may occur during preseason or during injury where nutrient intake may need to be altered to the needs of physical output. 157 This relationship is very important to the athlete's health and performance as it is often not reflected in BM measurement alone.…”
Section: Expert Group Topic 3: Body Compositionmentioning
confidence: 99%
“…The magnitude of this overload is largely dependent on previous experience with this technology as was shown by Tous-Fajardo et al [ 25 ], and the experience with these devices is crucial to optimize training. Previous studies using flywheel technology have shown benefits such us improved performance [ 24 , 28 , 29 ], chronic adaptations on muscular strength, power and gains in lean mass [ 28 30 ], higher force and power production combined with low energy expenditure [ 28 ] or reduced hamstring injuries in professional soccer players [ 11 , 22 , 28 ]. It should be noted that with the use of this flywheel technology a familiarization process is required and there is a lack of standard procedures for exercise loading prescription and limited evidence with elite athletes [ 28 ].…”
Section: Introductionmentioning
confidence: 99%